How to Develop Sustainable Irrigation Projects with Private Sector Participation - Mandri-Perrott, Cledan (World Bank, Washington, DC, 2016)
This is a handbook designed to guide governments, public authorities and other interested stakeholders in the process of designing and tendering sustainable Public-Private Partnership (PPP) arrangements in the irrigation sector. It takes a practical, step-by-step approach in describing what a government needs to do in preparing and implementing a PPP irrigation scheme from inception. The handbook takes account of the various stages of the irrigation value chain and how to handle private sector participation in irrigation schemes of different sizes and types. It assumes that governments have already made the underlying policy decision to embark on a PPP in irrigation, and therefore does not dwell on the rationale for undertaking a PPP. The handbook’s practical aspects are contained in four, stand-alone chapters that follow an over-arching Executive Summary and an Introduction. The chapters are deliberately numbered to coincide with the four steps that a government should take in establishing an irrigation PPP: Preparation, Structuring, Procurement Management, and Implementation. In addition, each chapter concludes with a practical Checklist to help executives keep track of the necessary tasks in each step on the way to establishing a sustainable PPP operation. The chapters are designed to be read as stand-alone guides, out of an understanding that institutions using the book may already have completed prior steps. Nevertheless, it would be prudent for users to acquaint themselves with the entire handbook so as to develop a holistic view of the requirements for a full PPP project. Chapter One: Preparation is divided into two parts, A and B (each with its own concluding Checklist). Part A reviews the scope for introducing PPPs into the irrigation sector, identifying the issues that policymakers should consider from the outset in order to make the private sector’s involvement feasible with a specific irrigation project.Part B discusses the irrigation as a business. It contains a variety of case studies—the first time such studies have been documented—with discussion of lessons learned, PPP types, transfer of investment functions in developing countries, competitive bidding, and third party involvement among the subjects covered. Chapter Two: Structuring a PPP sets out the various tasks that must be completed to structure a sustainable PPP contract. Chapter Three: Managing Procurement examines how to select a private contractor, which involves such factors as the fiscal commitments to the PPP, to what extent the process should be competitive and how that might be conducted and managed, and what issues are peculiar to PPPs in irrigation.Chapter Four: Implementation highlights management of the contract and establishment of those management structures, monitoring, penalties and grantor’s rights, use of performance bonds, enforcement of customer payments, dealing with changes to the contract, and contract expiry and asset handover. The overall structure of the handbook is illustrated below. The handbook is supported by three annexes: Annex 1 explains how to use the Excel Options Assessment Tool, , and Annex 2 provides case studies of 29 existing or emerging irrigation PPPs.